Kompor Gas Berbahan Bakar Biomassa - Fajri Vidian (Universitas Sriwijaya, 2009)
The rule of goverment for converting kerosene to gas made problem in rural to get gas. At this study have conducted modeling, manufacturing and testing a biomass gasification stove. The stove have 74.5 cm total height, 42 cm burner height, 16.5 cm diameter dan ash hopper . The results of eksperiment using rubber wood and cob as fuel showed stove could produce flame 30 until 40 minute with 4 until 6 for one bed fuel, the time for boiling water are 4 until 6 minute.